Sistem Pendukung Keputusan Pemilihan Dosen Terbaik dengan Menggunakan Metode VIKOR - Muhammad Khairil Kusuma; Nelly Astuti Hasibuan; Imam Saputra (Journal of Information System Research (JOSH), 2020)
Lecturer is a person who works as a lecturer in tertiary institutions. In the broad definition of lecturers, lecturers are professional and scientific educators with the main task of transforming, developing and disseminating science, technology and arts through education, research and community service. (Law-RI No.1 of 2005 article 1 (2) About Teachers and Lecturers). From this article 1 it should be emphasized that a lecturer is not only a professional educator at a university, but also a scientist. Decision support system is a computer base system that serves to assist decisions by utilizing data and models to solve unstructured problems in semi-structured within a company and organization, from some of these problems one of which is the Decision Support System for the Best Lecturer Selection STMIK Budi Darma Medan . From the problems faced, the use of a Keptusan Support System is expected to be the right solution. Because there are alternatives and criteria that can influence in a decision In this case the researcher used the Vikor method in selecting the best lecturer, believed to be able to solve the problems faced by STMIK Budi Darma Medan in choosing the best lecturer